PAI'S Digital Transformation for Millennial Students: Improving Religious Literacy Amid Social Media Distractions - Fakhiroh, Hana; Khobir , Abdul (The Future of Education Journal, 2025)
The development of digital technology has brought significant changes to the learning process, including in Islamic Religious Education (PAI). Millennial students, now part of Generation Alpha, are highly familiar with the use of gadgets and social media, potentially experiencing distractions that impact their religious literacy levels. This study aims to describe how digital transformation in Islamic Religious Education (PAI) learning can improve the religious literacy of millennial students amidst the strong influence of social media. Using a literature review method, this study examined various literature by collecting reference sources related to the research title. The results indicate that the use of technology such as digital learning platforms, interactive media, and multimedia-based religious content can increase students' interest and understanding of Islamic Religious Education (PAI) material. The digital transformation of PAI serves not only as a technical innovation but also as a pedagogical strategy that can reduce the distracting effects of social media by providing a more meaningful learning experience. This study emphasizes the importance of strengthening digital religious literacy as an effort to face the challenges of the social media era and ensure that religious values ​​remain internalized in millennial students.